ارزیابی تراکم عروق خونی در کیست فولیکولار، تومورادنتوژنیک کراتوسیست و آملوبلاستوما - صفورا سیفی; شهریار شفایی; سیاوش قدیری (Mashhad University of Medical Sciences, 2011)
Introduction: Ameloblastoma is a benign epithelial odontogenic tumor that exhibits a more aggressive behavior than follicular cyst and keratocystic odontogenic tumor. The purpose of the current study was detection and evaluation of microvessel density (MVD) effect on growth and clinical behavior of above odontogenic lesions with immunohistochemistry. Materials & Methods: In this descriptive-analytic cross-sectional study, 45 paraffin blocks of mentioned lesions were selected and stained immunohistochemically with CD34. The mean MVD of each lesionin three microscopic fields was calculated separately and was evaluated in the two areas, adjacent and far from odontogenic epithelium and then were compared with one another. Mann-Whiteny and Kruskal Wallis tests were used for the statistical analysis. Results: Mean microvessl density was 40.8±15.9, 25.4±5.3, and 9.4±3.52 in ameloblastoma, keratocystic odontogenic tumor , and follicular cyst, respectively.Mean microvessl density difference between the above mentioned lesions was statistically significant (P